2017
DOI: 10.3329/jninb.v2i2.34094
|View full text |Cite
|
Sign up to set email alerts
|

Digital Subtraction Angiography Findings in Aneurysmal Subarachnoid Haemorrhage: Experience of 30 Cases in Bangladesh

Abstract: Background: Digital subtraction angiography (DSA) is an important diagnostic tool for aneurysmal subarachnoid haemorrahage (SAH). Objectives: The purpose of the present study was to observe the findings of DSA in patients with SAH. Methodology: This cross-sectional study was performed in the Department of Neurology at Dhaka Medical College Hospital, Dhaka from December 2009 to November 2010 for a period of one (1) year. Patients at any age in both sexes who were admitted with SAH were included by purposive sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In Bangladesh a study of thirty SAH population revealed 44% of the patients had smoking habit and nearly half (46.7%) had hypertension 37 . Another study was conducted at Dhaka medical college and Hospital showed hypertension, smoking, diabetes mellitus and family history of SAH were found in 46.6%, 43.3%, 10.0% and 6.7% respectively 42 . Presence of risk factors in study population were more or less same with Bangladeshi research.…”
Section: Discussionmentioning
confidence: 97%
“…In Bangladesh a study of thirty SAH population revealed 44% of the patients had smoking habit and nearly half (46.7%) had hypertension 37 . Another study was conducted at Dhaka medical college and Hospital showed hypertension, smoking, diabetes mellitus and family history of SAH were found in 46.6%, 43.3%, 10.0% and 6.7% respectively 42 . Presence of risk factors in study population were more or less same with Bangladeshi research.…”
Section: Discussionmentioning
confidence: 97%